Navigating Indigenous Tradition and Modernity through Piduduk - Wilma Prafitri; Aris Setyoko; Zamrud Whidas Pratama (Digital Press Social Sciences and Humanities)
This study examines the intricate relationship between tradition and modernity by exploring piduduk, a cultural practice deeply embedded within indigenous communities. Piduduk serves as a vital medium for expressing ancestral wisdom, reinforcing social cohesion, and navigating the evolving challenges posed by contemporary societal transformations. Employing qualitative research methods, including in-depth interviews and participant observations, this study delves into the multifaceted meanings, symbolic representations, and functional roles of piduduk across various sociocultural contexts. A particular focus is placed on its role in shaping community identity, facilitating intergenerational transmission of knowledge, and serving as a mechanism for cultural resilience and resistance against the erosion of indigenous heritage. The findings indicate that piduduk is not only a reservoir of historical values but also a dynamic, adaptable activity that adapts to external influences while preserving its fundamental traditional essence. By bridging historical continuity with modern adaptation, piduduk exemplifies the ways in which indigenous communities actively negotiate their identities within an increasingly globalized world. This research contributes to a deeper understanding of the strategies employed by indigenous societies to preserve their cultural heritage while embracing change."Preserving" does not imply keeping culture static or frozen in time. Instead, it involves both protection and adaptation, allowing cultural elements to remain relevant while evolving alongside societal changes. Moreover, it underscores the broader significance of cultural practices in fostering community resilience, social cohesion, and knowledge sustainability